2019
DOI: 10.1021/acs.jced.9b01001
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibrium of Carbon Dioxide Hydrates Inhibited with MEG and NaCl above the Upper Quadruple Point

Abstract: Exploration of oil fields with high concentrations of carbon dioxide brings new challenges to the oil and gas industry. The high pressures reached in production pipelines can cause the condensation of the gas phase, characterizing the appearance of an upper quadruple point in the hydrate phase diagram. To prevent the formation of hydrates, the use of thermodynamic inhibitors, such as alcohols and glycols, is common in the industry. In addition, water from oil production is naturally inhibited with salts, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…(A) CO 2 hydrates equilibrium points with fresh water: experimental data of the present work (black circles) compared with literature data (pink diamond, green square, blue delta, and red left triangle) and (B) CH 4 hydrates equilibrium points with fresh water: experimental data of the present work (black circles) compared with literature data (blue delta, green square, pink left triangle, and red diamond).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…(A) CO 2 hydrates equilibrium points with fresh water: experimental data of the present work (black circles) compared with literature data (pink diamond, green square, blue delta, and red left triangle) and (B) CH 4 hydrates equilibrium points with fresh water: experimental data of the present work (black circles) compared with literature data (blue delta, green square, pink left triangle, and red diamond).…”
Section: Resultsmentioning
confidence: 93%
“…In this region, CO 2 is in a liquid phase, having a density analogous to that of the hydrate and liquid water phases. Therefore, the identification of the dissociation through widths of the volume, pressure, or temperature point is a dare since these variations in equilibrium are minor …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the equilibrium temperature of CH 4 hydrate in the presence of a 10 wt % monoethylene glycol and 10 wt % sodium chloride mixture was 271.1 K and reduced to 261.6 K due to the monoethylene glycol concentration increase to 30 wt %, at a pressure of 4.33 MPa. Cordeiro measured the CO 2 hydrate equilibrium data in the presence of concentrations of 10, 20, and 30 wt % ethylene glycol, 5 and 10 wt % sodium chloride salts, as well as a mixture of 5 wt % sodium chloride and 10, 20, and 30 wt % ethylene glycol in the pressure range of 8.5–25 MPa, using the isobaric method . The results showed that sodium chloride and ethylene glycol had a synergistic effect on the inhibitory power of CO 2 .…”
Section: Introductionmentioning
confidence: 99%